Leadership and Organizational Culture as Drivers of Effective Public Service Delivery - Okojie, Stephen O. (Advances in Social Sciences Research Journal, 2026)
This study examined the interplay between leadership practices and organizational culture as critical drivers of effective public service delivery in public-sector organizations. Despite the prevailing emphasis on structural reforms and performance metrics, this qualitative research highlights the significance of internal organizational dynamics in shaping service outcomes. The study involved in-depth interviews with 35 purposefully selected public-sector employees across various roles. Thematic analysis revealed four interrelated themes: leadership as a cultural cue; organizational culture as an interpretive lens for policy implementation; the role of ethics and accountability in fostering public trust; and the influence of discretion and power dynamics on service delivery. The Findings reveal that leadership influence is primarily exercised through daily sense-making rather than formal authority, with organizational culture mediating how policies are interpreted and enacted in practice. This research contributes to the public administration literature by integrating leadership and culture within an interpretive framework, emphasizing the importance of internal processes in understanding variations in public service delivery outcomes. The implications for leadership development, organizational learning, and governance reform are significant, underscoring the need to shift toward culturally informed leadership practices to enhance the efficacy of public service.